An ancient interlocus recombination increases class II MHC DQA diversity in sheep and other Bovidae. (June 2015) - Ballingall, Keith T.; Steele, Philip; Lantier, Isabelle; Cotelli, Matteo; Todd, Helen; Lopez, Guido; Martin, Elena; Lantier, Frederic
Summary Animals with fully characterised major histocompatibility complex (MHC) regions are often used to explore the molecular interactions that control the induction of adaptive immunity. The ovine MHC includes two DQA loci, termed DQA1 and DQA2. However, in a minority of haplotypes the DQA1 locus appears absent (DQA1 null) and is replaced by a second locus termed, DQA2‐like. This raises a number of questions regarding the origins and function of the DQA2‐like sequences. To address this, we have analysed DQA diversity associated with 10 MHC haplotypes, including two classified as DQA1 null. Pair‐wise comparison between full‐length DQA transcripts from each haplotype identified unique diversity throughout the DQA2‐like sequences. Conserved orthologues of the DQA2‐like sequences were identified in cattle and goat, and phylogenetic analysis clustered exons 1 and 2 with DQA2 whereas the remainder of the sequence clustered with DQA1. The DQA2‐like allelic lineage appears functional and to have arisen from an ancient interlocus recombination between DQA1 and DQA2 loci which predates Bovidae speciation.